PbS-CdS Thin Film Heterojunctions for Photovoltaic Applications - Singh, Kripal (My University, 2014)
Lead Sulfide (PbS) and Cadmium Sulfide (CdS) thin films were grown on the glass and indium tin oxide (ITO) coated substrates by chemical bath deposition (CBD) process. Lead acetate, cadmium chloride and thiourea were used in aqueous solutions as the ion sources of Pb, Cd and S. Films were grown for different durations ranging from 30 to 180 min at bath temperatures in the range of 30 to 80 C to determine the optimum film quality suitable for photovoltaic applications. The properties of the resulting thin films were characterized by various techniques such as X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM) and optical absorption measurements. Photovoltaic response was studied by fabricating Schottky (ITO/PbS/Al) and heterojunctions (ITO/CdS/PbS/Al) structures. It was found that at a low temperature of 30 C, it was not possible to grow the films irrespective of the deposition time. For the PbS films, deposition at 40 and 60C yielded films characterized by numerous holes for deposition times as long as 180 min, and hence, no photovoltaic response from those samples could be obtained. At 80 C, the films were dense, of polycrtsalline nature and showed a band gap of 1.4 to 1.6 eV, the most preferred one for the photovoltaic applications. Compared to PbS, the rate of dissociation of reagent compounds in the solution and formation of the compound on the substrate is faster for CdS for similar bath temperature. The band gap of the CdS films for a deposition time ranging from 30 to 160 min was in the range of 2.3 to 2.6 eV. From the current density – voltage curves of the fabricated heterojunction of the structure ITO/CdS/PbS/Al,very poor photovoltaic response was observed, possibly due to inferior film and interface properties.
Masters of Technology in Materials and Metallurgical Engineering-Thesis
Keywords: Chemical bath deposition; Sulfide thin films; Heterojunction; SPMS; Physics